Effects of seasonal training load on performance and illness symptoms in water polo - Brisola, G. M.; Claus, G. M.; Dutra, Y. M.; Malta, E. S.; de Poli, R. A.; Esco, M. R.; Zagatto, A. M. (The Journal of Strength and Conditioning Research, 2020)
The purpose of the study was to describe the training load distribution of a young female water polo team in different cycles of the season and verify its subsequent effects on specific fitness measured by the repeated sprints ability (RSA) test, aerobic endurance measured by the lactate minimum test, incidence and severity of upper respiratory tract infection (URTI) symptoms, and muscle damage markers. The training load (i.e., rating of perceived exertion × session duration) of 20 young female water polo players (mean ± SD: age = 15.65 ± 1.3 years; body mass = 60.93 ± 11.0 kg; height = 1.62 ± 0.1 m) was monitored, and the incidence and severity of URTI was assessed during part of the season. In addition, we assessed the lactate minimum speed (LMS), RSA, creatine kinase (CK), and lactate dehydrogenase (LDH) blood concentration during the season. The level of significance set was p < 0.05. The training loads were higher in the specific period (p < 0.01), whereas a high incidence of URTI was observed in the general cycle. The LMS was greater in the general cycle (p < 0.05), whereas total time and best time in the RSA test were greater in the competitive cycle (p < 0.05). The CK and LDH concentrations were significantly lower during the competitive cycle (p < 0.01). The general cycle of a female water polo team is critical regarding URTI and muscle damage, even with smaller training loads than the specific period.